2019
DOI: 10.5217/ir.2018.00167
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative histology-based classification system for assessment of the intestinal mucosal histological changes in patients with celiac disease

Abstract: Background/Aims The existing histological classifications for the interpretation of small intestinal biopsies are based on qualitative parameters with high intraobserver and interobserver variations. We have developed and propose a quantitative histological classification system for the assessment of intestinal mucosal biopsies. Methods We performed a computer-assisted quantitative histological assessment of digital images of duodenal biopsies from 137 controls and 124 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It was much higher than mean of total raised IEL of total cases at 24±15.73. This is similar to S.Pellegegrino et al, Biagi F et al, Jarvinen TT et al, Mokhtar et al and Prasenjit Das et al 8,[15][16][17][18] Thus higher villous tip IEL points towards the suggestive diagnosis of CD. Contrary to this Shmidt et al have observed no correlation between CD and numbers of IELs.…”
Section: Discussionsupporting
confidence: 82%
“…It was much higher than mean of total raised IEL of total cases at 24±15.73. This is similar to S.Pellegegrino et al, Biagi F et al, Jarvinen TT et al, Mokhtar et al and Prasenjit Das et al 8,[15][16][17][18] Thus higher villous tip IEL points towards the suggestive diagnosis of CD. Contrary to this Shmidt et al have observed no correlation between CD and numbers of IELs.…”
Section: Discussionsupporting
confidence: 82%
“…38,39 There has been an increasing interest in quantitative histological reporting, where the crypt depth, villous height, and number of intraepithelial lymphocytes per 100 epithelial cells are measured using a microscope with a calibrated micrometer. 37,38,40 We have recently reported a qualitative assessment of villous abnormalities using a computer-based quantitative assessment. 41 There is a need to increase awareness and training of the pathologists to adapt to the new system, which consumes more time but has higher objectivity, interobserver agreement, and reproducibility.…”
Section: Setting Up Of Facility For Diagnosis Of Cedmentioning
confidence: 99%
“…As this grading is based on visual impression of the reading pathologist, there is a high degree of interobserver and intraobserver variation in the assessment of the severity of villous abnormalities and, thus, poor reproducibility 38,39 . There has been an increasing interest in quantitative histological reporting, where the crypt depth, villous height, and number of intraepithelial lymphocytes per 100 epithelial cells are measured using a microscope with a calibrated micrometer 37,38,40 . We have recently reported a qualitative assessment of villous abnormalities using a computer‐based quantitative assessment 41 .…”
Section: Identification Of Challenges and Suggested Strategiesmentioning
confidence: 99%
“…On the other hand, this study could not confirm the existing data about villous and crypt lengthening in patients treated with GLP-2 (6-8). In the routine samples, mechanical artifacts and specimen orientation make a precise measuring of these structures difficult, even if oriented on cellulose acetate strips, as demonstrated by studies on duodenal biopsies in patients with coeliac disease, that recommend quantitative morphometric analysis for a reliable evaluation of villous length on routine biopsies (24)(25)(26)(27). In the same biopsies, we evaluated the immunophenotypic expression of S-phase marker (KI67 Mib-1) and proliferative inhibitors (p21 Kip-1 and p27 Waf-1) in our patient and in a small number of controls with regular morphology.…”
Section: Discussionmentioning
confidence: 99%